Anna Egorovna Dokuchaeva – the first Russian woman soil scientist - E. A. Rusakova (Бюллетень Почвенного института им. В.В. Докучаева)
In 2021 we celebrate the 175th anniversary of the birth of the founder of Soil Science – Vasiliy Vasilievich Dokuchaev, and his wife and colleague – Anna Egorovna Dokuchaeva (Sinclair). V.V. Dokuchaev personally highly appreciated the outstanding role of Anna Egorovna in the formation of the Russian school of soil scientists, calling her the first Russian woman soil scientist. The article is devoted to the life of A.E. Dokuchaeva and based on the analysis of a few archival materials and literature. He emphasized its importance not only in his own life and scientific work, but also noted its influence on the formation of young soil scientists. By the moment of the meeting with V.V. Dokuchaev, Anna Egorovna was an educated and financially independent woman, had teaching experience and was the head of a private girls’ school, that belonged to her, and led an active social life. A successful, active, but at the same time the fragile young woman, being the head of educational institution, became for her husband not just a loving and beloved wife, but also a loyal companion and assistant, in whom he always found understanding and encouragement, his reliable support. Anna Egorovna helped her husband with translations with scientific articles, participated with him in the preparation and work of the VIII Congress of Russian Naturalists and Doctors, traveled with Vasiliy Vasilievich on expeditions, and processed the materials collected. This is only a small part of what Anna Egorovna did in Soil Science and of what we know today from documents and memoirs, most likely her scientific activity was much wider. In the Dokuchaevs’ house, there was a close connection between the family and Anna Egorovna’s scientific activities, which only people close to the family, friends, and students of Vasiliy Vasilievich knew about, but for most people Anna Egorovna was not a scientist.